The Mediation of Job Satisfaction in Training Effect on Staff Performance - Hery Verianto The (Transpublika Publisher, 2025)
The capacity of work happiness to mediate the connection between training and performance has been the subject of conflicting results in other studies, the main purpose of this research is to dig out a better understanding of whether job satisfaction will be able to play such a role properly. This study applies a quantitative descriptive and causal approach. In this study, 79 people were chosen to participate as responders from the overall population. Using SPSS version 26, we evaluated the validity, reliability, and classical assumptions before diving into the deeper study. The ability of job satisfaction to act as a mediator was tested using a Sobel Test Calculator. With a p-value of less than 0.05, it seemed that work happiness may moderate the association between training and employee performance. The other three hypotheses were likewise verified to have a favourable and substantial effect. This study provides insight that implementing strategies to boost employee satisfaction can be more effective rather than only providing employees with training.